Evaluating the outcomes associated with an innovative change in a state-level transportation project prioritization process: A case study of Vermont. (August 2015) - Novak, David C.; Koliba, Chris; Zia, Asim; Tucker, Matt
Abstract: In this paper we examine the outcomes associated with an innovative change in a state-level transportation project prioritization process within the United States (U.S.). A foundational component of the innovation is the development and implementation of a novel multi-criteria analysis (MCA) tool to aid decision-makers. The pre and post-MCA project prioritization processes are described in detail for the state of Vermont, and we use a mixed methodological approach to empirically evaluate the outcomes associated with the innovative change with respect to three objectives: (1) to make the project prioritization process more transparent, (2) to improve the project prioritization process by incorporating well-defined, objective evaluation criteria into the decision-making process, and (3) to reduce inequality in the allocation of transportation project funds between the local jurisdictions. We demonstrate that the innovative change in the project prioritization process was clearly successful in accomplishing objectives 1 and 2, but does not appear to be successful with respect to accomplishing objective 3. The findings are discussed in the context of the state of Vermont, and we offer suggestions for how funding inequality might be addressed in the future. Highlights: Discuss policy issues related to state-level transportation funding in U.S. Consider multi-criteria analysis (MCA) to improve project prioritization process. Examine outcomes associated with an innovative public sector decision-making process. Discuss pre and post-innovation transportation project prioritization processes Evaluate inequality with respect to the distribution of transportation funds.